DEVELOPMENT OF THE LIVESTOCK INDUSTRY IN UKRAINE UNDER THE CONDITIONS OF SUSTAINABLE LAND USE AND CLIMATE CHANGE - KRASNORUTSKYY, Oleksiy; MARENYCH, Tetiana; SMIHUNOVA, Olena; KALCHENKO, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on analyzing the challenges and prospects for the development of Ukraine’s livestock industry under conditions of sustainable land use and climate change, as well as defining strategic directions for sectoral adaptation. The state of the livestock industry is highlighted, the main factors that determine the prospects for the sustainable development of livestock in the country are summarized. It is calculated that to meet the scientifically substantiated norm of milk and beef consumption per person per year, the total number of cattle would need to be increased to 6.31 million heads, which is 2.7 times more than in 2022. It is substantiated that sustainable land use management is the foundation for the development of livestock farming, and sustainable land use systems are a crucial tool in the fight against land degradation, climate change, and biodiversity loss. A significant factor contributing to the degradation of agricultural lands in Ukraine is the destruction of soil cover resulting from hostilities. It has been proven that the unsatisfactory state of land resources requires the adoption of effective measures to restore soil fertility and preserve it, which necessitates proper management, support, and protection. The priority measures for the restoration of fertility include the use of organic fertilizers, which dictates an increase in the number of farm animals, optimization of the structure of sown areas with proper crop rotation, anti-erosion methods of soil cultivation and modern soil protection technologies, as well as the expansion of irrigation and drainage areas. It is concluded that the development of precise mechanisms for implementing state tasks on the protection and rational use of agricultural lands, along with their implementation, will stimulate farmers to adhere to the principles of sustainable land use, thereby contributing to the revival and development of livestock farming. It is established that the use of agriculture to mitigate the effects of climate change remains a low priority in state support programs. To increase the sustainability and efficiency of livestock farming in agricultural enterprises in the face of modern challenges, it is proposed to highlight measures that intensify feed production, mitigate the consequences of war, and enhance the adaptive potential to climate change. Effective and consistent state support is recognized as a crucial condition for the development of sustainable land use and enhancing the efficiency of the livestock industry. It is assumed that in the medium term, the total consumption of milk, dairy products, and meat is unlikely to recover to the pre-war level due to the unfavorable demographic situation in the country.